The Effect of the Covid-19 Pandemic on Stress Learning - Salsabila, Qorri ‘Ainan; Aqinar, Zachrina; Effendi, Muhamad Ridwan (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2021)
Learning stress or academic stress is a category of distress in which students perceive academic demands as disturbing. It can also be interpreted as pressure related to the ability to master a science. Symptoms of learning stress include physical reactions, behaviour, thought processes, and emotions. Based on various research results, the level of learning stress increases during the COVID-19 pandemic. This is considered related to the change in the face-to-face learning system to online (in the network), which raises new factors as triggers for learning stress. This research was conducted to determine how the COVID-19 pandemic affects stress in learning and find solutions to overcome feelings of stress in learning, especially solutions from an Islamic perspective. The method used by the author in this study is a qualitative method with a literature study approach with analysis of the theory of Robert J. Van Amberg about the stages of stress. The results of the study revealed that learning stress factors during the covid-19 pandemic were in the form of lack of understanding of the material, a lot of assignments, declining grades, a tiring and boring learning system, quota constraints and internet networks, individual internal factors, and social factors other. Islam views stress as a trial that every Muslim must face. Islam also provides solutions for stress, namely patience, tawakkal, and the discipline of worship. Other solutions for learning stress during the COVID-19 pandemic can also be in the form of problem-focused coping and emotional focused coping, web-based Solution-Focused Brief Counseling (SFBC), and spiritual, emotional freedom technique (SEFT).